RESOURCE-SAVING TECHNOLOGY OF COMBINED DEFORMATION OF LOW-CARBON WIRE BASED ON SHEAR ROLLING COMBINED WITH DRAWING - PASHYNSKA, OLENA; ZAVDOVEEV, ANATOLIY; KRALYUK, MARYNA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The structure and properties of low-carbon wire 08G2S after two types of rolling are considered: hot shear rolling (RS) and standard hot rolling (ST), used for mass production of wire rod at  ArcelorMittal Kryvyi Rih PJSC. After different types of rolling, cold drawing (D) was carried out using the same conditions. Samples of two types were obtained: RS+D and ST+D. The physical and mechanical properties of materials were studied; established patterns of microstructure and fine structure formation. The work proved that there is a difference between the mechanisms of structure formation in RS and ST. The hereditary influence of the fine structure of steel after hot rolling on cold drawing processes is shown. With ST+D, grain refinement is observed with increasing degree of deformation. After RS+D there is no gradual refinement of grains with increasing degree of deformation. With RS+D, an alternation of fragmentation and low-temperature mechanically induced recrystallization occurs. The article shows that, provided that shear rolling technology is used, through the implementation of this structure transformation scenario, it is possible to obtain wire rod with improved properties without additional annealing.
Keywords: structure; properties; mechanisms; hot rolling; shear rolling; drawing